Scooby-Doo! and the creepy chef - McCann, Jesse Leon; Duendes Del Sur (Firm) (Edina, Minn. : Spotlight, 2010)
When they are invited to judge a cooking contest, Scooby-Doo and his friends at Mystery, Inc., wind up investigating the appearance of a creepy chef who is determined to sabotage the contest and spoil the event for everyone.
At head of title: Cartoon Network.
Keywords: Dogs -- Fiction; Cooking -- Competitions -- Fiction; School stories; Mystery fiction